Standardization of plant density and intra-row spacing to maximize seed size tubers in two potato cultivars (Solanum tuberosum) grown in northern hills - SINGH, RAJESH K; SHARMA, ASHWANI K; BUCKSETH, TANUJA; TIWARI, JAGESH K; CHAKRABARTI, S K (The Indian Journal of Agricultural Sciences, 2019)
To overcome the problem of oversize tubers, three planting densities (80000, 100000 and 133333 plants/ha) were evaluated at 25, 20 and 15 cm intra-row and 50 cm inter-row spacing, in two late blight resistant potato (Solanum tuberosum L.) cultivars, viz. Kufri Himalini and Kufri Girdhari during the kharif season under hill conditions. At the maximum plant density (133333 plants/ha) obtained with closer spacing (50 Ã— 15 cm), the proportion of extra large (>150 g) tubers was reduced from 23.5 to 12.4% in cv. Kufri Himalini and from 17.4 to 10.4% in cv. Kufri Girdhari. Besides, an increase in the proportion of seed size (20-80 g) tubers from 33.6 to 43.9% was also recorded. The yield of extra-large tubers (>150g) came down from 43 to 30% along with 10% increase in the yield of seed size (20-80 g) tubers.